Kegiatan Edukasi Pembelajaran Fiqih: Materi Rukun Islam melalui Metode Ceramah untuk Meningkatkan Kesadaran Beribadah Anak Usia Dini di TPQ Al-Hidayah, Pacar Kembang, Surabaya - Najibah, Mas Adelia (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
Fiqh learning education activities play an important role in improving early childhood worship awareness, particularly in understanding the pillars of Islam as the foundation of Islamic teachings. This study was motivated by the low level of children’s understanding of the pillars of Islam, which was caused by learning methods that were less engaging and less interactive. Therefore, this study aims to improve the understanding, habituation, and worship awareness of early childhood through the use of a simple, communicative, and easy-to-understand lecture method at TPQ Al-Hidayah, Pacar Kembang, Surabaya. This study employed a Participatory Action Research (PAR) approach consisting of several stages, namely problem identification, learning planning using the lecture method, implementation of activities, evaluation, and joint reflection to enhance learning effectiveness. The results showed that fiqh learning through the lecture method had a positive impact on improving children’s understanding of the pillars of Islam, developing worship habits, and fostering full awareness in carrying out daily worship practices. Thus, the lecture method is considered effective in enhancing understanding and worship awareness among early childhood learners.